Potential of Rare-Earth Compounds as Anticorrosion Pigment for Protection of Aerospace Aa2198-T851 Alloy - Espinoza-Vergara, J; Espinoza-Vergara, J (Elsevier Ltd, 2023)
In this study, the anticorrosion potential of carboxylic compounds; Lanthanum 4-hydroxycinnamate La(4OHCin)3, Cerium 4-hydroxycinnamate Ce(4OHCin)3 and Praseodymium 4-hydroxycinnamate Pr(4OHCin)3 for the protection of Al–Cu–Li alloy was investigated in 3.5% NaCl solution using electrochemical tests (EIS and PDP), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The findings achieved show a very good correlation between electrochemical responses and surface morphologies of the exposed alloy, indicating a modification of the surface by precipitation of the inhibitor species, leading to effective protection against corrosion. At optimum concentration 200 ppm, the trend of inhibition efficiency η (%) increases in the order Ce(4OHCin)3 93.35% > Pr(4OHCin)3 85.34% > La(4OHCin)3 82.25%. XPS complemented the findings by detecting and providing information about the oxidation states of the protective species. © 2023 The Authors